Do Living Arrangements and Social Network Influence the Mental Health Status of Older Adults in Malaysia? - Hamid, Tengku Aizan; Din, Hazwan Mat; Bagat, Mohamad Fazdillah; Ibrahim, Rahimah (Frontiers in Public Health, 2021)
Living arrangement has been reported to have a significant influence on several mental health statuses of older adults but their social network may confound this association. This study is aimed at examining the interactive effect of living arrangements and social network on the mental health status among older adults in Malaysia. A total of 2188 Malaysian older adults living nationwide were included in this cross-sectional study. Participants were classified into four groups according to their living arrangements (living alone or not living alone) and social network size (assessed using Lubben’s Social Network Scale-6). Poor social network was defined as the lowest quartile (4th quartile) of the score. Mental health statuses which include flourishing in life, life satisfaction, cognitive functions, loneliness, depression, and perceived stress, were measured. Multiple linear regression models, adjusted for age, gender, education, and comorbidities, revealed that a good social network was significantly associated with an increase on the flourishing scale scores, regardless of living arrangements. Not living alone and having good social network was significantly associated with increased Montreal Cognitive Assessment scores and decreased loneliness scores. This study found that living arrangements is not always a risk factor for the mental health status of older adults. However, it may be confounded by the level of their social networks. The results suggested that the effects of social network may exceed the impact of living arrangements. It is recommended that health professionals pay more attention to the social networks of older Malaysians to harness its benefits in improving their mental health status.